Salvage Procedure in Case of Urethrocavernous Fistula after Revision Surgery for Malfunctioning Three-Piece Penile Prosthesis - Enrico Caraceni; Angelo Marronaro; Luca Leone (Case Reports in Urology)
Urethrocavernous fistula is a rare complication of penile prosthesis. Literature lacks any materials regarding this complication’s treatment. We report our experience with a 66-year-old man who developed urethrocavernous fistula after penile prosthesis implant. Our technique involves the careful closure of urethral and corpus cavernosum defects with application of TachoSil® above the sutures. After the salvage procedure, no recurrence of fistula occurred and patient was able to have sexual intercourse. We believe that our technique may be successfully used in case of urethrocavernous fistula after penile prosthesis implant.